Um Estudo Sobre o Uso de Prompts LLM para a Avaliação da Acessibilidade Web dos Portais das Prefeituras da Região dos Sertões dos Crateús - França, Lúcio Cauper Freitas de; Andrade, Lisieux Marie M. dos S.; Carvalho, Windson Viana de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16064, 2025)
This study is an initial investigation into the use of Large Language Models (LLMs) with prompts written in Portuguese for web accessibility evaluation, using a set of 13 municipal government portals as a case study. ChatGPT 4o was employed to verify 37 success criteria from WCAG 2.2, and its coverage was compared with that of the automated inspection tools IBM, Achecker, andWAVE. Preliminary results indicate that the LLM provides positive contributions as a support tool in the web accessibility verification process.